KEPEMIMPINAN PENDIDIKAN VISIONER BERBASIS INOVATIF DALAM PENINGKATAN MUTU PENDIDIKAN - Siswadi, Siswadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This study addresses the role and influence of school principals' leadership in improving the quality of education in schools. Although many studies highlight the importance of school principals' leadership, challenges remain in optimizing this role, especially in responding to the dynamic and evolving educational  landscape.  Therefore,  this  research  aims  to  systematically  review  previous  studies  on  school  principals'  leadership  andits  impact  on educational quality.The method used is a systematic literature review following the PRISMA approach, involving the search and selection of literature based on inclusion criteria and employing the PICO method to ensure the relevance and quality of data sources. Data were collected from national scholarly articles published between 2020 and 2025 through the Google Scholar platform. The analysis synthesizes research findings related to leadership functions, leadership styles, as well as supporting and inhibiting factors in improving educational quality.The results indicate that school principals play a central role as managers, supervisors, motivators, and innovators capable of creating a conducive learning  environment  and  enhancing  teacher  professionalism.  Adaptive  and  visionary  leadership  has  proven  effective  in  addressing  educational challenges, including those posed by the pandemic. However, the effectiveness of leadership is influenced by the school context, available resources, and stakeholder support.